Postharvest losses and seed storage problems in major Sesame (Sesamum indicum L.) Growing states in India: Postharvest losses and seed storage problems in major Sesame (Sesamum indicum L.) Growing states in India - C MANIMURUGAN; P DURAIMURUGAN; J JAWAHAR LAL; K NATARAJAN; M KANWAT; R BISEN; M SUJATHA (Journal of Oilseeds Research, 2023)
A survey was conducted on postharvest losses and seed storage problems in sesame under farmers, oil extraction mills, mandi (government-regulated grain selling and procurement market) and warehouse conditions in major sesame growing states like Gujarat, Rajasthan, Madya Pradesh, Uttar Pradesh and Tamil Nadu. It was observed a minimum of 10% to a maximum of 25% postharvest losses from harvesting to transportation of seeds to processing/ washing plant for export purposes. These losses are mainly because of shattering while harvesting, spillage during transportation, improper handling in mandi and unscientific storage methods adopted by farmers and traders.